2009
DOI: 10.1179/acb.2009.050
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Outbreak in a Well-Vaccinated Nursing Home Population in Belgium

Abstract: Elderly people in nursing home communities are vulnerable to contagious infections, including the influenza virus. Systematic anti-influenza vaccination is an important preventive measure; however, vaccination does not provide absolute protection. We report an outbreak of influenza A infection in a well-vaccinated nursing home population. Several factors can facilitate the occurrence of this type of outbreak. This report mainly addresses the discrepancy between the circulating viral strain and strains present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…The article selection criteria allowed for inclusion of outbreaks occurring in assisted living facilities and nursing homes, which typically house individuals of different functional abilities. Only two outbreaks occurred among residents living exclusively in an assisted living facility 40,41 and one outbreak occurred in a combined assisted living-nursing home facility, 30 which were consistent with the remaining 58 outbreaks that occurred among residents of nursing homes. Moreover, our results appeared robust as case definitions were not associated with attack rates, and prophylactic vaccination of residents and staff was not related to antiviral use.…”
Section: Discussionsupporting
confidence: 62%
“…The article selection criteria allowed for inclusion of outbreaks occurring in assisted living facilities and nursing homes, which typically house individuals of different functional abilities. Only two outbreaks occurred among residents living exclusively in an assisted living facility 40,41 and one outbreak occurred in a combined assisted living-nursing home facility, 30 which were consistent with the remaining 58 outbreaks that occurred among residents of nursing homes. Moreover, our results appeared robust as case definitions were not associated with attack rates, and prophylactic vaccination of residents and staff was not related to antiviral use.…”
Section: Discussionsupporting
confidence: 62%
“…Fifteen studies reported outbreaks caused by bacteria [15-17, 20, 22, 24, 27, 32-39] and 22 studies were outbreaks by viruses [14,18,19,21,23,25,26,[28][29][30][31][40][41][42][43][44][45][46][47][48][49][50]. The largest number of a single pathogen was influenza viruses [40][41][42][43][44][45], followed by group A streptococcus (GAS) [17,20,24,37,38]. The most affected site was respiratory tract (n = 12) [32, 35, 36, 39-45, 48, 50], followed by gastrointestinal (GI) tract (n = 10) [14,16,23,26,27,31,33,46,47,49].…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
“…Three studies analyzed the data of multiple outbreaks of viral gastroenteritis and influenza-like illness that occurred in multiple facilities for a certain period of time [14,46,48]. The outbreaks in 23 studies affected both the residents and HCWs [14,20,22,23,25,26,29,31,33,[35][36][37][38][39][40][41][43][44][45][46][47][48][49], and the outbreaks of 14 studies affected only the residents [15-19, 21, 24, 27, 28, 30, 32, 34, 42, 50].…”
Section: Characteristics Of the Outbreaksmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza outbreaks have been regularly documented in long-term care facilities, including outbreaks of vaccine-matched influenza strains among highly vaccinated institutional populations. [202][203][204][205] Summer outbreaks of influenza also occur among elderly populations in long-term care facilities, [206][207][208] highlighting the year-round risk of transmission in institutionalized settings.…”
Section: Disease Burdenmentioning
confidence: 99%